A New Clinical Test to Evaluate Intrinsic Foot Muscle Function - Megna Panchbhavi BS; Michael C. Poliner MD; Patrick M. Finegan MD; Daniel C. Jupiter PhD (Foot & Ankle Orthopaedics)
Background: Intrinsic foot muscle weakness has been implicated in a wide range of forefoot conditions and is typically measured by the paper grip test. The proposed “knuckle test” is intended to evaluate intrinsic foot muscle function, in which active flexion of toes makes the metatarsal heads (“knuckles”) prominent in the forefoot. This study seeks to compare prevalence of negative knuckle test results and intrinsic muscle weakness in patients, primarily by association with a positive paper grip test result and secondarily with presence of toe deformities. Methods: Ninety-eight patients, 55 with toe deformity and 43 without, were evaluated for ability to flex their toes to the extent of knuckle prominence (knuckle test) and grip paper on the ground with their toes (paper grip test). Variables were compared between those with positive and negative knuckle test results. Results: A negative knuckle test result is significantly associated with the inability to grip a paper strip ( P  < .05). Conclusion: Given that the paper grip test outcomes are a well-established sign of intrinsic muscle weakness, the significant association between knuckle and paper grip test outcomes substantiates the use of the knuckle test to detect intrinsic muscle weakness. The knuckle test is a potentially quick, simple, and cost-effective clinical maneuver to indicate intrinsic foot muscle weakness in a patient. Level of Evidence: Level III, diagnostic test development.